Natal Fruit Fly, Natal Fly, Ceratitis rosa Karsch (Insecta: Diptera: Tephritidae) - Howard V. Weems, Jr.; Thomas R. Fasulo (EDIS)
The Natal fruit fly, Ceratitis rosa Karsch, was described in 1887 from specimens collected at Delagoa Bay, Mozambique. By 1900 it was recognized as a pest of orchard fruits throughout much of KwaZulu Natal Province, Republic of South Africa, and is considered to be the most common fruit fly of economic importance in Rhodesia. Following its accidental introduction into the island of Mauritius about 1953, this fly became firmly established and largely replaced the Mediterranean fruit fly, Ceratitis capitata (Wiedemann), as a pest of fruits. In South Africa the Natal fruit fly ranks second in importance only to the Mediterranean Fruit Fly, and at times it is an even more serious pest. This document is EENY-257 (originally published as DPI Entomology Circular 51), one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: January 2002.